Familial Aggregation of Schizophrenia: The Moderating Effect of Age at Onset, Parental Immigration, Paternal Age and Season of Birth - Svensson, Anna C. (Scand J Public Health, 2011)
AIM: An abundance of evidence has firmly established the familial aggregation of schizophrenia. The aim of this study was to examine how age at onset, parental characteristics and season of birth modify the familiality in schizophrenia. METHODS: A population-based cohort was created by linking the Swedish Multi-Generation and Hospital Discharge Registers. Among 5 075 998 full siblings born between 1932 through 1990, 16 346 cases of schizophrenia were identified. Familial aggregation was measured by the sibling recurrence-risk ratio, defined as the risk of schizophrenia among full siblings of schizophrenia patients compared with the risk among siblings of unaffected subjects. RESULTS: We found a statistically significantly lower recurrence-risk ratio in siblings of later onset cases (7.2; 95%CI 6.7-7.9) than of early onset cases (10.8; 95%CI 9.4-12.2). A lower recurrence-risk ratio was observed among offspring to fathers above 40 years (6.3; 95%CI 5.3-7.3) as compared with offspring of younger fathers (8.6; 95%CI 8.0-9.3). Further, among offspring to parents born outside Sweden the recurrence-risk ratio was statistically significantly lower (maternal immigrants 4.8; 95%CI 4.0-5.7, paternal immigrants 5.7; 95%CI 4.6-6.9) than among offspring to parents born in Sweden. CONCLUSIONS: The familial aggregation of schizophrenia was reduced by higher age at onset, advancing paternal age and immigrant status of parents.